2021
DOI: 10.1002/cncr.33488
|View full text |Cite
|
Sign up to set email alerts
|

Trends and racial disparities in aggressive end‐of‐life care for a national sample of women with ovarian cancer

Abstract: BACKGROUND The clinical landscape has moved toward less aggressive end‐of‐life care for women with ovarian cancer. However, whether there has been a decline in the use of aggressive end‐of‐life services is unknown. The authors evaluated current national trends and racial disparities in end‐of‐life care among women with ovarian cancer using the Surveillance, Epidemiology, and End Results‐Medicare–linked data set. METHODS In total, 7756 Medicare beneficiaries aged >66 years with ovarian cancer who died between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
2
18
2
Order By: Relevance
“…Compared with patients who receive the majority of their cancer care from a medical oncologist, those who receive the majority of their cancer care from a gynecologic oncologist are less likely to receive high-intensity care, but more likely to undergo invasive procedures at the end of life. Overall, both specialties engage in high levels of intense end-of-life care, with rates consistent with those previously reported 22–24. Similar to prior literature,16 most patients who experienced high-intensity end-of-life care experienced only one measure of aggressive care.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Compared with patients who receive the majority of their cancer care from a medical oncologist, those who receive the majority of their cancer care from a gynecologic oncologist are less likely to receive high-intensity care, but more likely to undergo invasive procedures at the end of life. Overall, both specialties engage in high levels of intense end-of-life care, with rates consistent with those previously reported 22–24. Similar to prior literature,16 most patients who experienced high-intensity end-of-life care experienced only one measure of aggressive care.…”
Section: Discussionsupporting
confidence: 85%
“…We found higher rates of invasive procedures at the end-of-life than what has previously been reported. Lower rates of invasive procedures in other literature may be due to variation in inclusion criteria, as there is no validated standard definition 7 23. Silber et al found no differences in operative procedures in the 5 years after the initial staging procedure by oncologist specialty 7.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,16,18 Independent binary measures for each outcome were created using Medicare claims data from the last 30 days of life on the basis of prior definitions and updated with International Classification of Diseases codes (ICD) 10th revision coding. 6,7,10 Physician Assignment Women were assigned to the physician they saw most for their ovarian cancer in an outpatient evaluation and management (E/M) setting. Encounters were classified as E/M using current procedural terminology codes beginning with 99 in the National Claims History Medicare claims file, and encounters were restricted to ovarian cancer by diagnosis code (ICD, 9th revision: 183, 1830, 18300, 18309, 1832, 1833, 1834, 1835, 1836, 1837, 1838, and 1839; ICD, 10th revision: C561, C562, and C569).…”
Section: Discussionmentioning
confidence: 99%
“…6 Trends in multiple end-of-life emergency department (ED) visits and intensive care unit (ICU) stays are increasing, whereas probability of aggressive treatments has not improved. 7 Why aggressive care for ovarian cancer at the end of life persists despite guidelines promoting more palliative care and less overuse of invasive treatments is not well understood? 4,5,8 Existing studies exploring end-of-life care for women with ovarian cancer have focused on the influence of patient characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Although populations with limited resources are less likely to receive palliative care, they are more likely to receive intensive end‐of‐life care, which may not be concordant with recommendations of guidelines 122‐124 . Among Medicare beneficiaries, for example, Black, Hispanic, and other women of color who died in 2007 through 2016 from ovarian cancer were more likely to be hospitalized or admitted in the intensive care unit at the end of life but were less likely to receive hospice care compared with White women 122 . Similarly, compared with White people, costs and hospital utilization during the month preceding death were greater among Black, Asian, and Hispanic people diagnosed with a lung cancer between 2000 and 2011 in another study 125 .…”
Section: Factors That Contribute To Cancer Disparities Across the Can...mentioning
confidence: 99%